2016
DOI: 10.1007/s12264-016-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

The Other Face of the Nucleus Accumbens: Aversion

Abstract: The nucleus accumbens (NAc) is thought to integrate information that is conveyed by (1) dopaminergic inputs from the midbrain and (2) glutamatergic inputs from limbic and cortical regions, including the amygdala, prefrontal cortex (PFC), hippocampus, and thalamus [1], and signal to the basal ganglia motor system to guide appropriate behaviors. Addictive drug use is proposed to hijack this system, enhancing the brain's reactivity to drug cues and triggering drug-seeking and relapse after prolonged withdrawal [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Stress/anti-reward system Besides the positive reinforcing effects of drug use, e.g., euphoria or "high," negative reinforcing effects associated with abstinence are also well-known factors that contribute to the development of drug addiction [2,56]. The negative reinforcement of drugs recruits a brain system that is opposed to the rewarding system, termed the anti-reward/stress system in the brain [2,57]. It is believed that the neuroanatomical substrate of the anti-reward system is the extended amygdala that includes the bed nucleus of the stria terminalis, the central amygdala, and the NAc shell [2,51].…”
Section: Trace Amine Systemmentioning
confidence: 99%
“…Stress/anti-reward system Besides the positive reinforcing effects of drug use, e.g., euphoria or "high," negative reinforcing effects associated with abstinence are also well-known factors that contribute to the development of drug addiction [2,56]. The negative reinforcement of drugs recruits a brain system that is opposed to the rewarding system, termed the anti-reward/stress system in the brain [2,57]. It is believed that the neuroanatomical substrate of the anti-reward system is the extended amygdala that includes the bed nucleus of the stria terminalis, the central amygdala, and the NAc shell [2,51].…”
Section: Trace Amine Systemmentioning
confidence: 99%
“…Besides, the NAc is also involved in the aversive emotional state linked to drug withdrawal, which induces continued and compulsive drug use. Inputs from the prefrontal cortex, ventral hippocampus, and basolateral amygdala to the NAc have been implicated in the rewarding effects of addictive drugs, while input from the paraventricular nucleus of the thalamus to the NAc mediates the physical changes and aversive memory induced by opiate withdrawal [2,3]. In addition, Wang et al [4] showed that both intraperitoneal injection of the D1 receptor antagonist, SCH23390, and intra-NAc injection of the MEK inhibitor, U0126, attenuate the propofol self-administration and diminish the expression of phosphorylated extracellular signal-regulated kinase (ERK) in the NAc.…”
mentioning
confidence: 99%